CS2 – MANTA – Multi-Functional Flap Mechanism (MFFM) offering a Second Degree of Freedom (2nd DoF) - Desmet, M.; Vervliet, J.; De Wit, D.; Everaert, B.; Seidler, R.; Docter, J.R. (ICAS, 2022)
In the frame of project MANTA or “MovAbles for Next generaTion Aircraft”, a Multi-Functional Flap Mechanism (MFFM) concept is developed for a novel wing lay-out which combines load alleviation, roll and high-lift functionalities into one large trailing edge control surface. The specific flap kinematics allows the multi-functional flap body to be rotated, at high speed, in any given flap position. Next to the concept description, the associated design challenges, aerodynamic effects and demonstration by test of the novel features are addressed towards a functional mechanism.